ASTEROSEISMIC ANALYSIS OF THE INTERNAL STRUCTURE AND EVOLUTION OF RED GIANT BRANCH BUMP STARS - Gai, Ning; Tang, Yanke (The Astrophysical journal, 2015)
ABSTRACT The "bump" is a prominent feature of the red giant branch (RGB) luminosity function of stellar clusters. Through constructing a grid of models with different masses and metallicities to study the feature of the RGB bump luminosity we find that the luminosity increases almost monotonically with increasing mass for a given metallicity and decreases monotonically with increasing metallicity. Moreover, different stars have different shapes of the RGB bump. It is correlated with the sharpness of the H discontinuity, which is left over by the convection envelope during the first dredge-up. Using the periodicity in the small separations d01, d10 to probe the internal structure, we find that, at about half the acoustic radius, the sound speed has a sharp variation that is caused by a local depression of the first adiabatic exponent in the second helium ionization zone. It induces an oscillation modulation in d01, d10 with a period of 6.4 Hz. Meanwhile, in the same model, the base of the convective envelope is located at a relatively small acoustic radius , which is about 10−1. It is too deep to detect the exact location of the bottom of the outer convective envelope. In order to discriminate the evolutionary status of different stars, we calculate the asymptotic g-mode period spacing . We find that decreases monotonically with evolution. It is a reliable parameter for distinguishing stars in different positions of the RGB bump.